AR-12 Has a Bactericidal Activity and a Synergistic Effect with Gentamicin against Group A Streptococcus - Nina Tsao (MDPI AG, 2021)
Streptococcus pyogenes (group A Streptococcus (GAS) is an important human pathogen that can cause severe invasive infection, such as necrotizing fasciitis and streptococcal toxic shock syndrome. The mortality rate of streptococcal toxic shock syndrome ranges from 20% to 50% in spite of antibiotics administration. AR-12, a pyrazole derivative, has been reported to inhibit the infection of viruses, intracellular bacteria, and fungi. In this report, we evaluated the bactericidal activities and mechanisms of AR-12 on GAS infection. Our in vitro results showed that AR-12 dose-dependently reduced the GAS growth, and 2.5 μg/mL of AR-12 significantly killed GAS within 2 h. AR-12 caused a remarkable reduction in nucleic acid and protein content of GAS. The expression of heat shock protein DnaK and streptococcal exotoxins was also inhibited by AR-12. Surveys of the GAS architecture by scanning electron microscopy revealed that AR-12-treated GAS displayed incomplete septa and micro-spherical structures protruding out of cell walls. Moreover, the combination of AR-12 and gentamicin had a synergistic antibacterial activity against GAS replication for both in vitro and in vivo infection. Taken together, these novel findings obtained in this study may provide a new therapeutic strategy for invasive GAS infection.